Post-operative outcome & disease-free survival among patients of breast cancer with raised C - reactive protein - Amir Iqbal Memon,; Aisha Masroor Bhatti,; Ramsha Khan,; Maira Sangrasi,; Sheraz Malik,; Hira Mughal, (International Journal on Women Empowerment, 2021)
Background: Cancer and inflammation have a bidirectional association; chronic inflammation is considered a major contributor to carcinogenesis. C - reactive protein (CRP), an inflammatory protein produced by the liver, has been identified as an important prognostic marker among breast cancer patients. This study aimed to elucidate the role of C-reactive protein as an inflammatory prognostic predictor in breast cancer patients and its impact on disease-free survival (DFS). Methodology: This prospective cohort study included 80 locally advanced breast cancer (stage II and III) patients presenting at the Department of General Surgery (Unit II), Liaquat University Hospital - Jamshoro/Hyderabad. Patient data, including demographics, stage and hormone status of breast cancer, metastatic workup, pre-operative CRP, post-operative complications and DFS on follow-ups including recurrence, metastasis and post-surgery skin manifestation, were recorded using a structured questionnaire. The statistical analysis was conducted on SPSS version 22.0. Results: Pre-operatively, a mildly raised serum CRP level was observed in 71.25% of patients and highly raised in 28.5%. The post-operative complications were observed in 12 participants with wound infection in 8, wound dehiscence in 3 and sepsis in only 1 participant. The DFS, including recurrence-free and metastatic-free survival, were observed in 69 participants Conclusion: After thorough observation, it can be concluded that the raised CRP level is a significant predictor for post-operative complications (wound infection, dehiscence, and sepsis) and disease-free survival among patients with locally advanced breast cancer.